Charge Behavior of Terminal Hydroxyl on Rutile TiO2(110) - Miyazaki, Masato (Langmuir : the ACS journal of surfaces and colloids, 2021)
Titanium dioxide (TiO2) is of considerable interest as a photocatalyst and a catalyst support. Surface hydroxyl groups (OH) are the most common adsorbates on the TiO2 surface and are believed to play crucial roles in their applications. Although the characteristics of bridging hydroxyl (OHbr) have been well understood, the adsorption structure and charged states of terminal hydroxyl (OHt) have not yet been experimentally elucidated at an atomic scale. In this study, we have investigated an isolated OHt on the rutile TiO2(110) surface by atomic force microscopy (AFM) and Kelvin probe force microscopy (KPFM). We found that OHt is in a negatively charged state. The unique characteristic of OHt is different from that of OHbr and involves the amphoterism and diversity of catalytic reactions of TiO2